The Development of Students' Spiritual Attitudes and Social Attitudes in Islamic Education and Civic Learning Through Religious Activities in Public Junior High School 2, 4 and 5 Cianjur Regency - Maspuroh Maspuroh; Uus Ruswandi; Aan Hasanah; Asep Nursobah (International Journal of Social Service and Research, 2022)
The purpose of this study was to determine the standard of educational assessment. student social. Second, to determine the learning process of developing spiritual attitudes and social attitudes in PAI (Islamic Education) learning, third to find out religious programs outside the classroom in developing spiritual attitudes and social attitudes. Fourth, reveal the supporting and inhibiting factors in the implementation of the development of spiritual attitudes and social attitudes through religious activities. Fifth, explore the results of developing spiritual attitudes and social attitudes inside and outside the classroom at Public Junior High School 2, 4 and 5 Cianjur. This research method is descriptive analytical. The results of this study are: (1) the learning process of PAI and Civics in developing spiritual attitudes and social attitudes Public Junior High School 2, 4, and 5 Cianjur has been carried out maximally with the support of all parties, (2) evaluations carried out by teachers at Public Junior High School 2, 4 and 5 on PAI and Civics learning carried out in the classroom, namely by objectively assessing students' abilities and competencies, (3) Religious activities at Public Junior High School 2, 4 and 5 have been carried out well, and (4) supporting factors in developing students' spiritual attitudes are schools working together with stakeholders, facilities and infrastructure that support these religious activities, 5. Learning models for developing spiritual attitudes and social attitudes at Public Junior High School 2, 4 and 5 Cianjur combine various learning models such as jigsaw, Gallery Walk, Debate, Discussion, Mind and Mapping.